Four weeks of power optimized sprint training improves sprint performance in adolescent soccer players - Derakhti, M.; Bremec, D.; Kambic, T.; Ten Siethoff, L.; Psilander, N. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This study compared the effects of heavy resisted sprint training (RST) versus unresisted sprint training (UST) on sprint performance among adolescent soccer players. Methods: Twenty-four male soccer players (age: 15.7 [0.5] y; body height: 175.7 [9.4] cm; body mass: 62.5 [9.2] kg) were randomly assigned to the RST group (n = 8), the UST group (n = 10), or the control group (n = 6). The UST group performed 8 × 20 m unresisted sprints twice weekly for 4 weeks, whereas the RST group performed 5 × 20-m heavy resisted sprints with a resistance set to maximize the horizontal power output. The control group performed only ordinary soccer training and match play. Magnitude-based decision and linear regression were used to analyze the data. Results: The RST group improved sprint performances with moderate to large effect sizes (0.76-1.41) across all distances, both within and between groups (>92% beneficial effect likelihood). Conversely, there were no clear improvements in the UST and control groups. The RST evoked the largest improvements over short distances (6%-8%) and was strongly associated with increased maximum horizontal force capacities (r = .9). Players with a preintervention deficit in force capacity appeared to benefit the most from RST. Conclusions: Four weeks of heavy RST led to superior improvements in short-sprint performance compared with UST among adolescent soccer players. Heavy RST, using a load individually selected to maximize horizontal power, is therefore highly recommended as a method to improve sprint acceleration in youth athletes.